Transforming into entrepreneurial university: cases from higher education institutions in Indonesia - Kurnia Endah Riana; Rini Dwiyani Hadiwidjaja; Yanuar Trisnowati; Minrohayati Minrohayati (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
This study explores the transformation of Indonesian state universities with legal entity status into entrepreneurial universities, using the OECD Guiding Framework for Entrepreneurial Universities as an analytical lens. Through an exploratory qualitative approach, it investigates institutional strategies, structures, and internal dynamics that shape innovation ecosystems. The study focuses on four universities—Institut Teknologi Bandung (ITB), IPB University, the University of Indonesia (UI), and Airlangga University—as case examples. The key finding highlights that while all four institutions have initiated entrepreneurial transformation, the degree of maturity varies significantly. IPB University exhibits the most comprehensive integration of entrepreneurial principles, particularly in research-based entrepreneurship. UI and ITB show substantial progress in innovation commercialization and industry collaboration, while Airlangga University is still in the early stages of ecosystem development. These differences illustrate how institutional context influences the pace and direction of transformation. A unique contribution of this research lies in its contextualized application of the OECD framework to Indonesian universities, offering practical insights into how global models can be adapted to national higher education settings. Strategic leadership, internal governance, and triple helix collaboration emerge as pivotal drivers of entrepreneurial transformation. Despite its insights, the study is limited by its focus on only four universities, which may not represent the full diversity of legal-entity universities in Indonesia. Future research should include broader samples and explore longitudinal changes to better understand the sustainability and scalability of entrepreneurial transitions in higher education.